Enhancing Community Participation at Local Development Projects in Bangladesh: Experience from Union Parishad Governance Project - Ara, Esmat; Seddiky, Md. Assraf; Basit, Abdul; Khanam, Ruba (European Scientific Journal, ESJ, 2024)
The study aimed to develop an approach for effective community participation in local development projects. Researchers conducted a field study in Sunamgonj district, one of the most vulnerable areas in Bangladesh, and collected information from Union Parishads (UP) chairpersons and members, secretaries, committee members, and local beneficiaries through interviews, and FGDs using purposive sampling and analyzed them employing thematic analysis method. Study findings revealed that although UP is considered as a close- knit community-based organization in terms of the nature of development work and geographic location, yet inclusive decentralization and democratic environment have not been established at the local level institutions for enhancing a meaningful community participation at local level development projects due to outsider interferences, nepotism, lack of knowledge and information, top-down bureaucratic decisions, gender discrimination, and corruption. It is believed that the model of meaningful decentralized participation system would help to mobilize the comprehensive local development process.